Hormone dependent uterine epithelial-stromal communication for pregnancy support. (December 2017) - Wang, Xiaoqiu; Wu, San-Pin; DeMayo, Francesco J.
Abstract: Human fertility is a relatively inefficient process. Despite the presence of visibly healthy embryos, 30% of pregnancies generated by assisted reproductive technology (ART) fail before the second trimester. The uterine microenvironment plays a critical role in establishing and maintaining a successful pregnancy that requires coordinated communication between the epithelial and stromal cells of the endometrium. The epithelial cells must cease proliferation and become permissive for the conceptus (embryo and associated extraembryonic membranes), while the stromal cells undergoes mesenchymal-to-epithelioid transformation to form the decidua in support of subsequent embryo development. The ovarian steroids Estrogen (E2) and Progesterone (P4) are the major hormones governing these processes. These hormones act via their nuclear receptors, the estrogen receptor, ESR1, and progesterone receptor, PGR, to direct the transcription of genes that orchestrate epithelial and stromal cell communication. This review will discuss the molecular mechanisms utilized by steroid hormones that regulate uterine receptivity, as well, establish and maintain pregnancy.